A Baedeker of decadence : charting a literary fashion, 1884-1927 - Schoolfield, George C. (Yale University Press, 2003)
"A Baedeker of Decadence presents an international collection of thirty-two works of literary decadence written between 1884 and 1927. George C. Schoolfield, a world authority on the decadent novel, offers an entertaining and wide-ranging commentary on the many strands of this highly significant literary and cultural phenomenon."--Jacket